Detection of Pig Cytochrome B in Beef Sausage Found in Traditional Markets around Jakarta - Dewi, Astria Prastika; Puspitasari, Riris; Perdana, Analekta Tiara (Prosiding SNPBS (Seminar Nasional Pendidikan Biologi dan Saintek), 2020)
Processed fast food products are currently in great demand by the people of Indonesia, especially with basic ingredients such as beef, chicken or other meats. Sausage is a fast food processed food that is at risk of mixing other food ingredients that can not be known by consumers. The halal of food products is considered very important by Muslim community and is taken into consideration in consuming food products. The food category in Indonesia still often mixes or falsifies halal food with prohibited ingredients, one of which is processed products such as sausages. Contamination of processed food products based on sausages was found to contain pig contamination circulating in the one of market in Indonesia by testing as many as 5 out of 6 sausage samples were detected positively contaminated with pig which resembled a Polymerase Chain Reaction (PCR) product sequencing results of 95% with Sus scrofa species. The purpose of this study is to detect pig contamination in processed food products such as sausages sold in traditional markets and modern markets and the benefits of this research to detect cytochrome b pig genes in sausages and provide information to the public about the halal status of sausages on the market. The research method uses the PCR Technique which is able to be used as a tool to detect contamination of other meats with using a pig specific primer. Sausage samples was obtained from around Jakarta. DNA of pigs and bovine was extracted as positive and negative controls, as well as testing all of sausage samples. The results showed that from all of sausage samples amplified by PCR there were no pig cytochrome b genes. This finding informed that the sausages collected from market around Jakarta were negative to pig components.